A Simple and Clean Method for Methoxymethylation of Phenols - Ahmad, Faujan; Bruce, Malcolm J. (1989)
A simple and clean procedure for the preparation of methoxymethyl ethers (MOM = CH2 OMe) of phenols having internally hydrogen bonded hydroxy groups is described. Thus treatment of 2,5-dihydroxybenzaldehyde (1) with a 1:1 mixture of methoxymethyl chloride-methyl acetate in ether at room temperature gives 2.5-bis( methoxymethoxy)benzaldehyde (2) in 57% yield; under similar conditions, the methoxymethyl ether (6) of salicylaldehyde was isolated in 75% yield. Yields of61-81 %, not optimised, of methoxymethyl ethers of several phenols lacking internal hydrogen bonding were also obtained.